Pandemic power grab - Guasti, P; Bustikova, L (Taylor and Francis, 2022)
Is Covid-19 undermining European democracies? Recent scholarship overlooks the fact that most pandemic-related erosions of democracy can be attributed to illiberal inertia long in place before 2019. Did the democratic decay occur during the pandemic or due to the pandemic? We analyse the extent to which pandemic power grabs succeeded and failed in Europe with special attention to the Czech Republic, Hungary, Poland, and Slovakia. The executive power of the purse was an opportunity to abuse state resources. Governments that engage in the “pandemic heist” with impunity can be directly linked to a power grab due to the pandemic.